(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the skills of using ICT and the ability to use them in their work are an integral part of the competence of translation, that is, they are part of the information competence of the students. Also, the use of ICT is necessary in the preparation and execution of exercises for teaching simultaneous translation, because teachers use Internet resources (listed in research or found independently) to find different types of real texts, the necessary voice recordings (for exercises such as shadowing ) should be used. Students should use online dictionaries, glossaries, and self-study resources. In the process of organizing simultaneous translation training, it is necessary to follow the goals achieved by the exercises. The goal of our methodology is to build the translation competence of a simultaneous interpreter, so the set of exercises used in the training process is aimed at developing and improving all components of this competence.